2015
DOI: 10.1074/jbc.m115.645689
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Stereospecificity of Bacterial B12-dependent 2-Hydroxyisobutyryl-CoA Mutase

Abstract: Background: Bacterial B 12 -dependent 2-hydroxyisobutyryl-CoA mutase specifically catalyzes the isomerization of (S)-3-hydroxybutyryl-and 2-hydroxyisobutyryl-CoA. Results: The crystal structure of 2-hydroxyisobutyryl-CoA mutase shows decisive differences in the active site when compared with the well studied methylmalonyl-CoA mutase. Conclusion: Specificity toward (S)-3-hydroxybutyryl-CoA strongly depends on the active site amino acid Asp A117 . Significance: This is the first structural characterization of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…Substrate-bound structures of MCM (25,26) and HCM1 (29) as well as bioinformatic analyses (4,6,11,13) have suggested that substrate specificity in acylCoA mutases is determined by the identity of a few key amino acids. Indeed, HCM1 carrying a single active site mutation has both considerable PCM and HCM2 activity and reduced HCM1 activity (29). All other attempts to rationally alter the substrate specificity of acyl-CoA mutases by mutagenesis, however, have failed (13,34), indicating that our understanding of substrate specificity in acyl-CoA mutases is incomplete.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate-bound structures of MCM (25,26) and HCM1 (29) as well as bioinformatic analyses (4,6,11,13) have suggested that substrate specificity in acylCoA mutases is determined by the identity of a few key amino acids. Indeed, HCM1 carrying a single active site mutation has both considerable PCM and HCM2 activity and reduced HCM1 activity (29). All other attempts to rationally alter the substrate specificity of acyl-CoA mutases by mutagenesis, however, have failed (13,34), indicating that our understanding of substrate specificity in acyl-CoA mutases is incomplete.…”
mentioning
confidence: 99%
“…Of these acyl-CoA mutases, only MCM (24 -27), IcmF (28), and HCM1 (29) have been structurally characterized, and only MCM and HCM1 have been visualized with substrates bound. All three enzymes require two domains for catalytic activity as follows: a Rossmann-fold cobalamin (Cbl)-binding domain, which binds the AdoCbl cofactor in the "base-off/His-on" mode (24,27,30), and an (␣/␤) 8 triose-phosphate isomerase (TIM) barrel, which binds the substrate.…”
mentioning
confidence: 99%
“…Likely most interesting, Gln A208 of HCM is replaced by Ser in RCM. Thus, considering the active-site architecture of HCM (27), changes to Val and Ser at positions 117 and 208, respectively, might result in a preferred binding of (R)-3-hydroxybutyryl-CoA as observed for RCM in this study. However, a precise description of the active-site architecture of RCM cannot simply be derived from sequence alignments; models based on crystal structure analysis are required.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, an RCM-like but less-pronounced reversion of stereospecificity has recently been obtained with an HCM variant possessing the single point mutation Asp A117 to Val A117 . Although having the same amino acid residue at position HcmA 117 as found in RCM, conversion of (R)-3-hydroxybuytryl-CoA by this enzyme, i.e., HcmA D117V reconstituted with wild-type HcmB, is not as efficient as by RCM, but only a 5-times-higher catalytic efficiency than for the (S)-enantiomer has been observed (27). This weaker reversion indicates that not only the HcmA residue at position 117 but likely also substrate interactions with other active site amino acids contribute to stereospecificity in HCM enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation